Production of multiwall carbon nanotube for alcohol sensor application / Ebtehal Saleh Alshaqaq - Alshaqaq, Ebtehal Saleh (2010)

(untitled)
Multiwall carbon nanotube/polyethylene oxide (PEO), multiwall carbon nanoube/polyvinyl alcohol(PVA) and multiwall carbon nanotube/ polyvinyl alcohol(PVA)/zinc oxide(ZnO) have been tested as chemical sensors and detailed study on the effect of different gas concentration and material properties on gas sensitivity is presented. Initial composites were prepared by a simple solution casting and characterized by x-ray diffraction for ZnO, Fourier transform infra-red spectroscopy (FTIR) and scanning electron microscopy (SEM) to demonstrate crystallite size of ZnO, the morphology and surface area respectively. On the other hand, MWCNT/PEO , MWCNT/PVA , MWCNT/PVA/ZnO were prepared with different loading MWCNT and ZnO. The chemical sensing properties of the composites were investigated by exposure to methanol vapor with different concentration (1.7, 3.3, 5,8.3 and 16.7vol% in water). The sensing experiment proved that the sensitivity of the composites increase due to amount of CNT and the highest value to the sensitivity was at composites with ZnO. It was discovered that for all composite systems, the highest sensitivity was recorded at moderate methanol concentrations in water of about 5%. For MWCNT/PVA composite, sensitivity increased with MWCNT loading as expected. The highest recorded was about 250% for 5% MWCNT loading detecting 5% methanol in water. Similar result was obtained with MWCNT/PVA/ZnO composites with 1% MWCNT and 3% ZnO, indicating the significant role of ZnO in methanol detection.